2022
DOI: 10.1111/liv.15240
|View full text |Cite
|
Sign up to set email alerts
|

m5C and m6A modification of long noncoding NKILA accelerates cholangiocarcinoma progression via the miR‐582‐3p‐YAP1 axis

Abstract: Cholangiocarcinoma (CCA) is a severe malignancy originating from the bile duct and the second most common primary liver cancer. NF‐kappa B interacting lncRNA (NKILA) is a functional lncRNA, which play important role in human cancers. However, the role and underlying mechanism of NKILA in CCA remains largely unknown. Here, our study demonstrated that NKILA was significantly upregulated in CCA tissues and cells. Overexpression of NKILA is associated with advanced TNM stage, lymph node and distant metastasis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…95 Previous studies have indicated the role of NSUN2 role in regulating lncRNA m5C methylation in esophageal squamous cell carcinoma, hepatocellular carcinoma (HCC), and cholangiocarcinoma. 45,94,96,97 However, the roles of NSUN2 methylated lncRNAs in BC are rarely clarified, which needs further investigation. Analysis of TCGA data, encompassing normal adjacent tissues and BRCA tumor tissues, revealed significant upregulation of NSUN2, NSUN5, DNMT1, DNMT3A, and DNMT3B, and downregulation of TRDMT1 and TET2 in BC, supported by protein-protein interaction networks and coexpression analysis, indicating internal correlations among m5C regulator genes.…”
Section: Roles Of Lncrnas In Bc Epitranscriptomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 Previous studies have indicated the role of NSUN2 role in regulating lncRNA m5C methylation in esophageal squamous cell carcinoma, hepatocellular carcinoma (HCC), and cholangiocarcinoma. 45,94,96,97 However, the roles of NSUN2 methylated lncRNAs in BC are rarely clarified, which needs further investigation. Analysis of TCGA data, encompassing normal adjacent tissues and BRCA tumor tissues, revealed significant upregulation of NSUN2, NSUN5, DNMT1, DNMT3A, and DNMT3B, and downregulation of TRDMT1 and TET2 in BC, supported by protein-protein interaction networks and coexpression analysis, indicating internal correlations among m5C regulator genes.…”
Section: Roles Of Lncrnas In Bc Epitranscriptomicsmentioning
confidence: 99%
“…As a crucial cytosine‐C(5)‐methyltransferase, NOP2/SUN RNA methyltransferase 2 (NSUN2) governs tumorigenesis and progression by influencing m5C modification in diverse RNAs, including mRNAs and lncRNAs 95 . Previous studies have indicated the role of NSUN2 role in regulating lncRNA m5C methylation in esophageal squamous cell carcinoma, hepatocellular carcinoma (HCC), and cholangiocarcinoma 45,94,96,97 . However, the roles of NSUN2 methylated lncRNAs in BC are rarely clarified, which needs further investigation.…”
Section: Roles Of Lncrnas In Bc Epitranscriptomicsmentioning
confidence: 99%
“…YBX1 is another m 5 C reader that has multiple functions in cancer development and embryo development. Oncogenic effects of YBX1 are found in GC ( 51 ), bladder cancer ( 100 ), glioblastoma ( 101 ), CRC ( 76 , 102 ), cholangiocarcinoma ( 103 ), clear cell renal cell carcinoma (ccRCC) ( 104 ), prostate cancer ( 56 ), epithelial ovarian cancer ( 105 ) and cervical cancer ( 57 ), mainly owing to YBX1-RNA interactions that have stabilizing effects on target RNAs. For example, in GC patients, YBX1 binds with FOXC2 (Forkhead box protein C2) mRNA, which is m 5 C-modulated by NSUN2, to enhance its tumor-promoting ability ( 51 ).…”
Section: The Mechanism and Basic Biological Functions Of M ...mentioning
confidence: 99%
“…The m 5 C levels of peripheral blood immune cells showed higher CRC diagnostic value than that of common blood tumor biomarkers ( 76 ), which is correlated with the discovery that m 5 C modification inhibits tumor infiltration of immune cells ( 133 ). In cholangiocarcinoma patients, the m 5 C-modified functional lncRNA NKILA (NF-kappa B interacting lncRNA), which is recognized and stabilized by YBX1, is associated with advanced TNM stage and poor prognosis ( 103 ). In glioma patients, m 5 C-associated genes, including NSUN1-5, NSUN7, DNMT1, DNMT3B and YBX-1, are upregulated, with the exception of NSUN6 ( 63 , 101 , 134 ).…”
Section: C Rna Modification In Cancer Cellsmentioning
confidence: 99%
“…It promotes hepatocellular carcinoma (HCC) cell migration, invasion, and angiogenesis by increasing the m 5 C modification of H19 long noncoding RNA (lncRNA) in the nucleolus, followed by promoting the binding of the m 5 C‐modified H19 long noncoding RNA (lncRNA) to the oncoprotein G3BP1 in the cytoplasm (Sun et al, 2020). NSUN2‐dependent m 5 C modification also participates in the metastasis of cholangiocarcinoma (CCA), another common primary liver cancer, by upregulating the level of m 5 C and promoting the interaction between m 5 C and YBX1 on NF‐kappa B interacting lncRNA (Zheng et al, 2022). Moreover, small ubiquitin‐like modifier‐2/3‐modified NSUN2 aggravates gastric cancer metastasis by regulating m 5 C modification on mRNA (Hu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%